Reimagining the peer‐review system for translational health science journals - Elise M. Smith (Wiley, 2021)
Abstract Retractions of coronavirus disease 2019 (COVID‐19) papers in high impact journals, such as The Lancet and the New England Journal of Medicine, have been panned as major scientific fraud in public media. The initial reaction to this news was to seek out scapegoats and blame individual authors, peer‐reviewers, editors, and journals for wrong doing. This paper suggests that scapegoating a few individuals for faulty science is a myopic approach to the more profound problem with peer‐review. Peer‐review in its current limited form cannot be expected to adequately address the scope and complexity of large interdisciplinary science research collaboration, which is central in translational research. In addition, empirical studies on the effectiveness of traditional peer‐review reveal its very real potential for bias and groupthink; as such, expectations regarding the capacity and effectiveness of the current peer review process are unrealistic. This paper proposes a new vision of peer‐review in translational science that, on the one hand, would allow for early release of a manuscript to ensure expediency, whereas also creating a forum or a collective of various experts to actively comment, scrutinize, and even build on the research under review. The aim would be to not only generate open discussion and oversight respecting the quality and limitations of the research, but also to assess the extent and the means for that knowledge to translate into social benefit.